Humeral Head Reconstruction of Reverse Hill-Sachs Lesions With Osteochondral Allograft - Kyle T. Deivert MD; Jelle P. van der List MD, PhD; Nicholas A. Trasolini MD, FAAOS; Brian R. Waterman MD, FAAOS (SAGE Publishing, 2024)
Background: True confirmed posterior shoulder dislocations are relatively uncommon injuries, with an estimated incidence of 1.1 per 100,000 individuals and are initially missed in up to 50% to 80% of cases. There are several treatment options for this injury presentation. In this case, we will focus on reconstruction with osteochondral allograft. Indications: If the cartilage cannot be fixed due to comminution or the cartilage is not viable due to chronicity or impact, osteochondral allograft might be a treatment option. This technique is typically considered for defects involving greater than 35% to 40% of the humeral head. Technique Description: The anterior defect on the humeral head was exposed on the cadaver specimen. Circular bone plugs were obtained from a distal femur specimen for grafting. Graft sites were prepared with a 15 reamer with an orthogonal approach to avoid oblique entry for a stacked bone plug configuration. Bone plug grafts were placed in the defect via press-fit fixation. The subscapularis is repaired to the lesser tubercle following the reconstruction. Results: Various studies reported improvement in pain, shoulder range of motion, and patient-reported outcome scores. A small percentage of patients developed allograft necrosis. Patients who received autografts had lower rates of osteoarthritis than patients who received allograft. Rehab protocol can last up to 12 months and begins with restricted range of motions and slowly advancing to isometric movements and gradually increasing range of motion and strengthening. Discussion/Conclusion: Outcomes described in previous studies are limited due to the low incidence of these injuries and small sample size. Missing the initial posterior dislocation as this is often correlated with inferior outcomes when treated in chronic setting. There is a risk of damage to humeral articular cartilage during osteochondral tissue harvesting so care must be taken during tissue harvest. Older, lower-demand patients have been reported to do well with nonoperative treatment, even in the case of a chronic dislocation, so careful discussion with the patient is needed to not perform surgery in a reasonably functioning non-painful shoulder. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.